Representative Farms Economic Outlook for the January 2016 FAPRI/AFPC Baseline - James W. Richardson; Joe L. Outlaw; George M. Knapek; J. Marc Raulston; Brian K. Herbst; David P. Anderson; Steven L. Klose (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2016)
The Agricultural and Food Policy Center (AFPC) at Texas A&M University develops and maintains data to simulate 94 representative crop, dairy, and livestock operations in major production areas in 29 states. The chief purpose of this analysis is to project the economic viability of those farms by region and commodity for 2016 through 2020. The data necessary to simulate the economic activity of these operations is developed through ongoing cooperation with panels of agricultural producers in selected states. The Food and Agricultural Policy Research Institute (FAPRI) provided projected prices, policy variables, and input inflation rates in their January 2016 Baseline. Under the January 2016 Baseline, 27 of the 63 crop farms are considered in good liquidity condition (less than a 25 percent chance of negative ending cash by 2020). Ten crop farms have between a 25 percent and a 50 percent likelihood of negative ending cash, and the remaining 26 crop farms have greater than a 50 percent chance of negative ending cash. Additionally, 25 of the 63 crop farms are considered in good equity position (less than a 25 percent chance of decreasing real net worth during the study period). Six crop farms have between a 25 percent and 50 percent likelihood of losing real net worth, and 32 crop farms have greater than a 50 percent probability of decreasing real net worth by 2020. The following discussion provides an overall evaluation by commodity considering both liquidity and equity measures. FEEDGRAIN FARMS: Ten of the 23 feedgrain farms are in good overall financial condition. Two farms are classified in marginal condition, and eleven are in poor condition. WHEAT FARMS: Four representative wheat farms are classified in good overall financial condition, one is in marginal condition, and six are in poor condition. COTTON FARMS: Three of the 15 cotton farms are classified in good condition, four are in marginal condition, and eight are in poor condition. RICE FARMS: Nine of the 14 rice farms are projected to be in good financial condition. One rice farm is projected to be in marginal condition; four are in poor condition. DAIRY FARMS: Twelve of the 20 dairies are in good overall financial condition. Four are classified in marginal condition, and four are in poor condition. BEEF CATTLE RANCHES: Two of the 11 cattle ranches are classified in good financial condition, eight are in marginal condition, and one is projected to be in poor condition.
Keywords: 330